Palm Oil Taxation and Environmental Justice: Fiscal Policy Challenges in Indonesia (Indonesian Tax Justice Review, 2025)
Indonesia is the world’s largest producer of palm oil, generating significant export revenues while simultaneously contributing to environmental degradation and social inequality. This paper examines Indonesia’s palm oil taxation policies through the combined lenses of tax justice and environmental justice. Using legal and policy analysis, the study evaluates export levies, corporate income taxation, and sector-specific fiscal incentives applied to palm oil producers. The findings indicate that existing tax instruments inadequately internalize environmental externalities and disproportionately favor large-scale corporate producers. Smallholders often face compliance burdens without corresponding fiscal support or redistributive benefits. The paper argues that the current fiscal framework fails to align revenue mobilization with sustainability and equity objectives. The global contribution of this study lies in linking commodity taxation with environmental justice concerns in developing countries integrated into global supply chains. Indonesia’s experience illustrates how sector-specific tax policy can reinforce global environmental inequality by allowing environmental costs to be externalized to local communities. The study contributes to international tax justice literature by advocating for integrated fiscal-environmental approaches that combine taxation, redistribution, and environmental accountability. These findings are relevant for other commodity-dependent economies seeking to design tax policies that support both development and sustainability goals.